- 4

- 0

## Main Question or Discussion Point

Hi i really need help with dealing with logs:

log x - log x = 2

3 9

so i change the base, since 9 is a power of 3.

y = log_9(x)

Then

9^y = x

(3^2)^y = x

3^(2y) = x

2y = log_3(x)

log_3(x)

y = --------

2

Now i have

log_3(x)

log_3(x) - -------- = 2

2

but i am really stuck with dealing with the x please help!!!!!

log x - log x = 2

3 9

so i change the base, since 9 is a power of 3.

y = log_9(x)

Then

9^y = x

(3^2)^y = x

3^(2y) = x

2y = log_3(x)

log_3(x)

y = --------

2

Now i have

log_3(x)

log_3(x) - -------- = 2

2

but i am really stuck with dealing with the x please help!!!!!